Highly potent antimicrobial polyionenes with rapid killing kinetics, skin biocompatibility and in vivo bactericidal activity. (May 2017) - Liu, Shaoqiong; Ono, Robert J.; Wu, Hong; Teo, Jye Yng; Liang, Zhen Chang; Xu, Kaijin; Zhang, Musan; Zhong, Guansheng; Tan, Jeremy P.K.; Ng, Michelle; Yang, Chuan; Chan, Julian; et al.
Abstract: Effective antimicrobial agents are important arsenals in our perennial fight against communicable diseases, hospital-acquired and surgical site multidrug-resistant infections. In this study, we devise a strategy for the development of highly efficacious and skin compatible yet inexpensive water-soluble macromolecular antimicrobial polyionenes by employing a catalyst-free, polyaddition polymerization using commercially available monomers. A series of antimicrobial polyionenes are prepared through a simple polyaddition reaction with both polymer-forming reaction and charge installation occurring simultaneously. The compositions and structures of polymers are modulated to study their effects on antimicrobial activity against a broad spectrum of pathogenic microbes. Polymers with optimized compositions have potent antimicrobial activity with low minimum inhibitory concentrations of 1.95–7.8 μg/mL and high selectivity over mammalian cells. In particular, a killing efficiency of more than 99.9% within 2 min is obtained. Moreover, the polymers demonstrate high antimicrobial efficacy against various clinically-isolated multidrug-resistant microbes, yet exhibit vastly superior skin biocompatibility in mice as compared to other clinically used surgical scrubs (chlorhexidine and betadine). Microbicidal activity of the polymer is mediated via membrane lysis as demonstrated by confocal microscopy. Unlike small molecular antibiotics, repeated use of the polymer does not induce drug resistance. More importantly, the polymer shows excellent bactericidal activity in a P. aeruginosa -contaminated mouse skin model. Given their rapid and efficacious microbicidal activity and skin compatibility, these polymers have tremendous potential to be developed as surgical scrubs/hand sanitizers to prevent multidrug-resistant infections. Graphical abstract: